Satellite Cell Expression of RAGE (Receptor for Advanced Glycation end Products) Is Important for Collateral Vessel Formation - Laura Hansen; Giji Joseph; Alejandra Valdivia; W. Robert Taylor (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background The growth and remodeling of vascular networks is an important component of the prognosis for patients with peripheral artery disease. One protein that has been previously implicated to play a role in this process is RAGE (receptor for advanced glycation end products). This study sought to determine the cellular source of RAGE in the ischemic hind limb and the role of RAGE signaling in this cell type. Methods and Results Using a hind limb ischemia model of vascular growth, this study found skeletal muscle satellite cells to be a novel major cellular source of RAGE in ischemic tissue by both staining and cellular sorting. Although wild‐type satellite cells increased tumor necrosis factor‐α and monocyte chemoattractant protein‐1 production in response to ischemia in vivo and a RAGE ligand in vitro, satellite cells from RAGE knockout mice lacked the increase in cytokine production both in vivo in response to ischemia and in vitro after stimuli with the RAGE ligand high‐mobility group box 1. Furthermore, encapsulated wild‐type satellite cells improved perfusion after hind limb ischemia surgery by both perfusion staining and vessel quantification, but RAGE knockout satellite cells provided no improvement over empty capsules. Conclusions Thus, RAGE expression and signaling in satellite cells is crucial for their response to stimuli and angiogenic and arteriogenic functions.